General analysis of polarization observables in the reaction... - Gakh, A.G. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2011)
A general analysis of expressions for polarization observables in the reaction of coherent pseudoscalar meson electroproduction on deuteron has been derived. This analysis does not depend on details of reaction mechanisms since it based on general symmetry properties of the electromagnetic interaction with hadrons. Expressions for the following polarization observables have been obtained: the asymmetries caused by the vector or tensor polarized deuteron target, the spin correlation coefficients which describe the dependence of the cross section on deuteron target polarization and longitudinal polarization of the electron beam and the asymmetry due to the longitudinal polarization of the electron beam. The experimental situation, when final deuteron and scattered electron are detected in coincidence, has been considered. Выполнен общий анализ выражений для поляризационных наблюдаемых в реакции когерентного электрообразования псевдоскалярного мезона на дейтроне. Этот анализ не зависит от деталей механизмов реакции, так как он основан на общих свойствах симметрии электромагнитного взаимодействия адронов. Получены выражения для следующих поляризационных наблюдаемых: асимметрии, обусловленные векторной или тензорной поляризациями дейтронной мишени; коэффициенты спиновой корреляции, которые описывают зависимость сечения от поляризации дейтронной мишени и продольной поляризации электронного пучка; асимметрия, обусловленная продольной поляризацией электронного пучка. Рассмотрена экспериментальная постановка опыта, когда конечный дейтрон и рассеянный электрон детектируются на совпадение. Виконано загальний аналіз виразів для поляризаційних спостережуваних у реакції когерентного електроутворення псевдоскалярного мезона на дейтроні. Цей аналіз не залежить від деталей механізмів реакції тому що він базується на загальних властивостях симетрії електромагнітної взаємодії адронів. Отримані вирази для наступних поляризаційних спостережуваних: асиметрії, які обумовлені векторною або тензорною поляризаціями дейтронної мішені; коефіцієнти спінової кореляції, які описують залежність переріза від поляризації дейтронної мішені та повздовжньої поляризації електронного пучка; асиметрія, яка обумовлена повздовжньою поляризацією електронного пучка. Розглянута експериментальна постановка коли кінцевий дейтрон і електрон який розсіюється детектуються на збіг.
Keywords: polarization observables; cross section; asymmetry; electron; deuteron; meson electroproduction; поляризационные наблюдаемые; сечение; асимметрия; электрон; дейтрон; электрообразование мезона